(untitled) (Revista de História da UEG (REVHIST), 2020)
This study has as aim to show the relevance of the women’s participation in the Paraguayan War (1864-1870) and the Retreat of Laguna War (1867). In this context, it is also intended to discuss the tenuous history of women, given that, for decades, by the traditional historiography that it has had the supremacy of the male perspective. The method used was deductive, with extensive bibliographic research in specialized works about the proposed thematic. It was analyzed the question of the invasion on the South of the Province of Mato Grosso-MT, Brazil, by Solano López troops. D. Senhorinha is highlighted, due to her resilience, emphasizing the importance of the presence of other women who carried out the most diverse activities in support of imperial troops, especially those called “vivandeiras”, suffering the misfortunes and adversities that permeated this war, the issue of female prostitution in daily relations and, still, a small mention to the destined and resident women of Paraguay. In this way, we sought to unveil the mist that still surrounds this important and expressive participation of Brazilian and Paraguayan women during the Paraguayan War. Keywords: Paraguayan War. History of women. “Vivandeiras”.